Agricultural Production Challenges in Latakia Governorate A Field Study from the Perspective of a Sample of Farmers - الحداد, خلدون (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The aim of this research is to identify the main problems facing agricultural production in Latakia Governorate, which are (scarcity of resources, climate change, diseases and pests, weak marketing, weak government support), through application to a sample of farmers in the regions of Latakia Governorate. The research employed a descriptive approach. The research population included all farmers in the regions of Latakia Governorate (Latakia, Jableh, Qardaha, and Jableh regions). The research sample was a random sample of 300 farmers from the governorate's regions. Interviews were conducted with the farmers, and a questionnaire was distributed as a research tool. A total of 263 complete and valid questionnaires were retrieved, representing a response rate of 89%. The research findings revealed that agricultural production in Latakia Governorate faces a range of challenges, with resource scarcity at the forefront, followed by weak marketing, weak government support, climate change, and finally, diseases and pests.